Implementation of Interpretative Structural Modeling In the New Normal Era at SMAN 1 Matur - Roby Candra Roby Canda; Iswandi Umar (Jurnal Kependudukan dan Pembangunan Lingkungan, 2021)
Education during a pandemic needs to implement a learning system that can combine face-to-face learning, online learning, offline learning, and implementing health protocols. One of the approaches used in this study uses interpretive structural modeling with a group assessment process where structural models are generated to photograph complex matters. of a system, through carefully planned patterns using graphs and sentences. The results obtained explain the findings related to learning constraints from the internet network, hardware, and application constraints causing students to be late in submitting assignments, as well as having difficulty finding reading resources around their homes. The implementation of geography learning in the new normal era requires guidance to students before understanding the use of applications in learning the new norm era.